Liver involvement in Gaucher disease type I: a retrospective single-center study from Ukraine - Samonenko, Nataliia; Olkhovych, Nataliia; Okhotnikova, Olena; Gorovenko, Nataliia (Frontiers in Medicine, 2025)
BackgroundGaucher disease (GD) type I is a rare lysosomal storage disorder characterized by systemic manifestations including hepatosplenomegaly, cytopenias, and skeletal complications. Although liver involvement is common, its clinical significance and diagnostic potential remain underexplored.ObjectivesTo analyze the spectrum of liver involvement in Ukrainian patients with type I Gaucher disease and to evaluate its clinical, biochemical, and diagnostic significance throughout the course of the disease.MethodsWe retrospectively analyzed medical records of 89 patients with confirmed GD who were monitored at the National Children’s Specialized Hospital “Okhmatdyt” (Kyiv, Ukraine) between 2001 and 2023. Type I Gaucher was confirmed in 82 patients. Diagnosis was established through enzymatic and molecular genetic testing. Liver enlargement, hepatic structural changes, laboratory markers, ultrasound findings, and serum ferritin levels were assessed, with comparative analysis between patients with and without splenectomy.ResultsHepatomegaly was observed in 91% of patients with GD type I. Despite liver enlargement, only 2.4% of patients demonstrated elevated transaminases, and no hyperbilirubinemia was reported, indicating preserved hepatic function. Additional liver pathology (steatosis, fibrosis, hemangiomatosis, cysts, or cholecystitis) was present in 45% of cases. A strong correlation was identified between the degree of hepatomegaly and elevated ferritin levels. Cholelithiasis was significantly more prevalent among splenectomized patients (42% vs. 17%; OR = 4.25; p = 0.014).ConclusionLiver involvement in GD type I is common, multifaceted, and may not always be reflected in standard liver function tests. While hepatocellular function is typically preserved, structural liver abnormalities are frequently observed. Serum ferritin may serve as an auxiliary marker of disease activity. The results emphasize the need for comprehensive hepatic monitoring in GD and support the potential value of neonatal screening for early detection and management.